Adoption of Big Push hypothesis: evidence from the case of Botswana. (19th November 2009) - Conrad, Christopher; Kulkarni, Kishore G.
Rosenstein-Rodan proposed that if expansionary and developmental policies have to be pursued, the small changes in fiscal and monetary policy make minor changes in economic growth. So, if a meaningful economic development is the objective carrying out Big Push is necessary for the policy makers. This hypothesis is in line with Keynesian advice that 'a somewhat comprehensive socialisation of investment is the only means of approximation to the full employment', which was adopted diligently by many economies especially in the developing world. This paper is an attempt of applying the Big Push hypothesis for the policies of Botswana. It reviews the relevant literature in early sections and summarises the argument of Big Push hypothesis. In later sections, it applies the hypothesis to Botswana case and concludes that the Big Push hypothesis has in fact made an impact on the economy's development.